Multifunctional property analysis of 3D-printed composite scaffolds from PLA/PCL filaments with graphene oxide reinforcement - Eryildiz, Meltem; Karakus, Aleyna; Altan, Mihrigul Eksi (WILEY, 2025)
This study investigates the multifunctional properties of three-dimensional (3D)-printed Polylactic acid (PLA) and Poly-epsilon-caprolactone (PCL) scaffolds reinforced with graphene oxide (GO) for advanced biomedical applications utilizing the fused filament fabrication method. PLA/PCL (80:20) was selected for its balance of stiffness and flexibility, while GO was incorporated at varying concentrations (0.5 weight percent (wt%), 1, 2, and 3 wt%). Composite filaments were produced through melt blending and extrusion, with subsequent 3D printing to create scaffolds. Fourier transform infrared spectroscopy analysis at 1 wt% GO revealed optimal functional group interactions. Differential scanning calorimetry and thermogravimetric analysis showed significantly enhanced thermal stability and crystallinity, while mechanical tests demonstrated 41.9% and 15% improvements in tensile and compressive strengths, respectively. Scanning electron microscopy analysis indicated morphological differences in the PLA/PCL matrix with increasing GO content. Rheological analysis indicated that lower GO concentrations led to an optimal viscosity, enhancing processability and maintaining structural integrity, with 1 wt% providing the best balance between ease of flow and mechanical stability. These findings highlight the potential of GO-reinforced PLA/PCL scaffolds for biomedical applications, identifying 1 wt% GO as the optimal concentration for achieving superior thermal, mechanical, and rheological properties.Highlights GO-reinforced PLA/PCL filaments were successfully produced for scaffolds. GO enhances PLA/PCL scaffold strength, stability, and processability. 1 wt% GO improves thermal, mechanical, and rheological properties. GO boosts thermal stability, crystallinity, and structural integrity. SEM reveals PLA/PCL matrix changes with increasing GO content.
Keywords: 3D printing; 3D-printed scaffolds; biomedical scaffolds; graphene oxide; PLA/PCL; polymer composites; NANOPARTICLE; Materials Science; Polymer Science